A King Stifling Voices of Dissent? Popular Protests and State Responses in Xi's China. (15th April 2021) - Wang, Hsin‐Hsien; Tzeng, Wei‐Feng; Wang, Shinn‐Shyr; Chiu, Wei‐Chih
Abstract : To deal with the increases in the frequency of popular protests, China's leader, Xi Jinping, has called for "innovative social governance" as a new concept to resolve social conflicts. In this study, we collect and analyze a unique dataset to compare state responses to popular protests during Xi's term and Hu's term. We find that, under Xi's rule, state repression is more frequently employed to handle social disturbances. Violent protests are significantly more likely to be repressed than nonviolent protests during both the rule of Hu and Xi, while protests that involved a population of the middle and upper classes experienced more state crackdown under Xi's rule rather than under Hu's governance. Our empirical analysis suggests that the approaches by which the Chinese government deals with social unrest have not yet been "innovative." Instead, China still relies heavily on despotic power in the Xi era.